Perilaku Rangka Open Web Truss Joist LVL Sengon - Basuki, Achmad; Awaludin, Ali; Suhendro, Bambang; Siswosukarto, Suprapto (Department of Civil Engineering, Diponegoro University, 2021)
Laminated Veneer Lumber (LVL) Sengon is classified as one of the engineering products having a significant increase of both physical and mechanical properties compared with Sengon solid wood. Considering its short planting years and sustainable production, Sengon wood is very potential to be used as construction materials of low-rise houses to support the housing needs in Indonesia. Creep behaviour of LVL Sengon material is one of the mechanical properties that needs to be considered. This article evaluated value of creep factor of the open web truss joist (OWTJ) LVL Sengon test and compared this experimental creep factor with the numerical results developed by FE model taking into account the viscoelastic parameters of authors' previous study. The viscoelastic parameters were based on a 217-day creep test of compression and tension parallel to the grain of LVL Sengon at 20 % of stress level that were further modeled using Prony series creep model having n equals to 3. The reduction in the modulus of elasticity over time resulted in creep deflection and creep factor values at 217 days of testing results and FE numerical analysis of the OWTJ LVL Sengon ranging from 1.50–1.54; while the predicted creep factor at 25 years of service life is 1.57 or greater than the creep factor value provided in SNI 7973: 2013 of 1.5.